Механизм формирования эффективной материальной мотивации персонала (Путеводитель предпринимателя, 2020)
The article concerns various components of material motivation. It focuses on main material incentives which impact efficiency of labour. Authour presents results of research of a company’s staff which can be usefull in development of effective system of financial incentives. It also describes the process of creating material motivation mechanism.